Pediatric Shock Profile in The Pediatric Intensive Care Unit (PICU) of Dr. Soetomo General Academic Hospital - Anshori, Rafida; Setyaningtyas, Arina; Utariani, Arie; Kusumastuti, Neurinda Permata (Indonesian Journal of Anesthesiology and Reanimation, 2023)
Introduction: Shock is a life-threatening condition caused by circulatory failure which increases morbidity and mortality rate. According to the western literature, about 2% of children are admitted to hospitals worldwide due to shock. Objective: This study aimed to describe the pediatric shock profile of patients in the Pediatric Intensive Care Unit (PICU) of Dr. Soetomo General Academic Hospital between 1 January to 1 December 2019. Methods: A total of 60 patients were selected as the participants using a descriptive method. Data collection was carried out by recording the exact time the participants first entered the PICU. Furthermore, data were collected based on gender, age, physical and laboratory examination, diagnosis of shock, patients' outcomes, as well as PRISM III score. Results: The results of this study that the males and children are 51.7% and 53.3%, respectively. At an infant age, the distribution of the highest average pulse and breathing frequency was 135 and 32.2, respectively. The highest average body temperature at the age of adolescents was 37.19°C. Furthermore, the patients' diagnoses were dominated by distributive shock with the highest PRISM III score â‰¥8 and deaths recorded of 76.6%, 60%, and 61.7%, respectively. The diagnosis results showed that distributive shock leads to the highest mortality with a PRISM III score of 51.7% and 53.3%. Conclusion: Distributive shock contributes to the patient's diagnoses and mortality rate with the highest score of PRISM III being â‰¥8. From this conclusion, the PICU needs to be more responsive to detect distributive shock in children.